O trabalho de assistentes sociais na Educação Profissional e Tecnológica: desvelando seu processamento no Instituto Federal de São Paulo (IFSP) - Dantas, Maria Conceição Borges (2020)
The thesis has as object of study the work of the social worker in professional and technological education, focusing on the Federal Institute of São Paulo (IFSP). The study of this theme gains relevance due to the growing insertion of social workers, mainly from the 2000s, in the Education Policy, due to the expansion policies of the Federal Network of Professional, Scientific and Technological Education. Such expansion was driven by the access and permanence policies expressed, among others, in Decree no.7234/2010 PNAES and Law no. 12711/2012 – known as the Quota Law, which expands possibilities and challenges to carry out professional work, based on the principles and guidelines of the Social Work ethical-political project. The main objective of the study was to analyze the processing of the work of social workers at the Federal Institute of São Paulo, seeking to explain its contents and meanings. The research was guided by the hypothesis that the way in which the Student Assistance Policy has been assumed buy the IFSP has led to a simplification of professional work through predominantly bureaucratic-administrative activities that limit the possibilities of building broader professional responses, focusing on relative professional autonomy an in the consolidation of a certain institutional “place” of Social Work. The study was carried out through bibliographic, documentary and field research, with the realization of focus groups and semi-structured interviews with social workers professionals from the IFSP, in addition to the analytical treatment of institutional documents that standardize and define guidelines for carrying out the professional work in the institution. As a main result of the research, a double reductionism was identified in relation to Student Assistance, the main institutional requisition, which directly impacts the processing of the work of the social worker. This reductionism is materialized, either by the restricted understanding of student assistance aimed at the almost exclusive execution of the Permanence Aid Program, with an emphasis on bureaucratic-administrative activities rather than activities of a socio-educational nature; either because such procesuality has caused a downgrade of the intellectual and creative dimension of professional work, reducing it to simple work, in Marx’s terms. This whole context has hindered the institutional agents’ understanding of professional attributions and competences, reflecting in a movement of “de-professionalization” of the social worker activity